A comparison of C-F and C-H bond activation by zerovalent ni and pt: a density functional study. - Reinhold, M; McGrady, J; Perutz, R (2004)
Density functional theory indicates that oxidative addition of the C-F and C-H bonds in C6F6 and C6H6 at zerovalent nickel and platinum fragments, M(H2PCH2CH2PH2), proceeds via initial exothermic formation of an eta2-coordinated arene complex. Two distinct transition states have been located on the potential energy surface between the eta2-coordinated arene and the oxidative addition product. The first, at relatively low energy, features an eta3-coordinated arene and connects two identical eta2-arene minima, while the second leads to cleavage of the C-X bond. The absence of intermediate C-F or C-H sigma complexes observed in other systems is traced to the ability of the 14-electron metal fragment to accommodate the eta3-coordination mode in the first transition state. Oxidative addition of the C-F bond is exothermic at both nickel and platinum, but the barrier is significantly higher for the heavier element as a result of strong 5dpi-ppi repulsions in the transition state. Similar repulsive interactions lead to a relatively long Pt-F bond with a lower stretching frequency in the oxidative addition product. Activation of the C-H bond is, in contrast, exothermic only for the platinum complex. We conclude that the nickel system is better suited to selective C-F bond activation than its platinum analogue for two reasons: the strong thermodynamic preference for C-F over C-H bond activation and the relatively low kinetic barrier.